Pengaruh Stres Kerja Dan Kompensasi Finansial Terhadap Kepuasan Kerja Driver Gojek Ride Di Kecamatan Duren Sawit-Jakarta Timur - Salsabila, Silvia; Ekawaty, Novian (Peneliti.net, 2024)
This study aims to examine and analyse the partial and simultaneous influence of job stress (X1) and Financial Compensation (X2) on Job Satisfaction (Y) of Goek Ride Driver in the Duren Sawit District-East Jakarta. The study was conducted by selecting a population of 306 Gojek Ride Drivers in The Duren Sawit District-East Jakarta, then a sample of 173 Gojek Ride Drivers Obtained Using the Slovin Formula. The chosen technique was probability sampling, specifically a technique known as proportional stratified random sampling. This research employed a descriptive analysis method with a quantitative approach. Statistical analysis was processed with the help of SPSS software, version 29. This research discovered that the variable work stress (X1) has an average score of 554,3 with the criteria of moderately agree. Financial Compensation (X2) has an average value of 496,6 with the criteia of moderately agree, and job satisfaction has a score of 577,1 within the category of moderately agree as well. The variables work stress (X1) and Financial Compensation (X2) contribute partially to influence at a magnitude of 18,6% and 42,6% respectively. Furthermore, both of these independent variables also collectively influence the dependent variable at a simultaneous level of 53,6%. The remaining 46,4% influence was given by the other variables which were not examined within this study.